1984
DOI: 10.1113/jphysiol.1984.sp015085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition from the brain stem of inhibitory interneurones of the cat's dorsal lateral geniculate nucleus.

Abstract: SUMMARY1. Brain-stem control of inhibitory circuits in the dorsal lateral geniculate nucleus (d.l.g.n.) of the cat was studied with extracellular recordings from functionally identified interneurones and with intracellular recordings from principal cells.2. Perigeniculate neurones, the recurrent inhibitory interneurones of the d.l.g.n., were inhibited by low-threshold stimulation within a wide bilateral field of the brainstem reticular formation extending from the rostral mesencephalon to the caudal medulla ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 26 publications
4
44
1
Order By: Relevance
“…An early in vivo study has shown that activation of brainstem cholinergic cells, which project to the thalamic nuclei, can induce a large hyperpolarization in geniculate interneurons (Ahlsén et al, 1984), caused presumably by activation of a potassium conductance (McCormick and Pape, 1988). Here, we show that in addition to a potassium conductance, activation of muscarinic receptors also enhances I h and I CAN .…”
Section: Muscarinic Receptor-mediated Responses In Thalamic Interneuronsmentioning
confidence: 56%
See 1 more Smart Citation
“…An early in vivo study has shown that activation of brainstem cholinergic cells, which project to the thalamic nuclei, can induce a large hyperpolarization in geniculate interneurons (Ahlsén et al, 1984), caused presumably by activation of a potassium conductance (McCormick and Pape, 1988). Here, we show that in addition to a potassium conductance, activation of muscarinic receptors also enhances I h and I CAN .…”
Section: Muscarinic Receptor-mediated Responses In Thalamic Interneuronsmentioning
confidence: 56%
“…Activation of the cholinergic input from the brainstem, which occurs during arousal, affects sensory transmission in the thalamus (Sillito et al, 1983;Francesconi et al, 1988;Heggelund, 1994, 1995;Uhlrich et al, 1995). In particular, inhibitory sharpening of sensory information is dramatically altered during the activation (Ahlsén et al, 1984;Hu et al, 1989;Murphy et al, 1994). In vitro studies have shown that various neuromodulators change the membrane potential of reticular and thalamocortical cells (Steriade et al, 1997), which switches their firing patterns by inactivating or deinactivating a low-threshold calcium current crucial for burst firing (Huguenard, 1996).…”
Section: Abstract: Rat; Thalamus; Interneurons; Inhibition; Cholinermentioning
confidence: 99%
“…Possible involvement of ACh in the ascending control of arousal Electrophysiological recording (Steriade, Oakson & Ropert, 1982), stimulation (Moruzzi & Magoun, 1949;Symmes & Anderson, 1967;Satinsky, 1968;Foote et al 1974;Kitsikis & Steriade, 1981;Ahlsen, Lindstr6m, & Lo, 1984;Francesconi et al 1984) and lesion (Watson, Heilman, Miller & King, 1974) experiments (also see reviews by Steriade, 1970;Singer, 1977;Burke & Cole, 1978) have indicated the presence of an ascending brain-stem system which has the ability to control the level of neuronal excitability in both the thalamus and cerebral cortex. The possibility that the brain-stem influences may be mediated, at least in part, by the activation of ACh-releasing neurones has been suggested by a number of investigators (Singer, 1977;Steriade & Deschenes, 1984;Sherman & Koch, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Dubin & Cleland, 1977;Lindstrom, 1982), and the third from intrageniculate interneurones (Dubin & Cleland, 1977;but see Friedlander, Lin, Stanford & Sherman, 1981). An indirect input through both the perigeniculate nucleus and the intrageniculate interneurones comes from the mesencephalic reticular formation (Singer, 1977;Ahlsen, Lindstrom & Lo, 1984). It has been suggested that the variability of relay cells depends upon activity in the reticular formation (e.g.…”
Section: Sources Of Variabilitymentioning
confidence: 99%